Penerapan Model Pembelajaran Problem Based Learning (Pbl) Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Pada Siswa Kelas IV SD Gmim 1 Madidir - Mandey, Steven; Pati, Lucia A. M.; Omega, Ticoalu Trivena Anggun (Peneliti.net, 2024)
This study aims to improve the learning outcomes of Indonesian language of grade IV students of SD GMIM 1 Madidir through the Problem Based Learning (PBL) learning model. This study uses a classroom action research (CAR) method consisting of four stages, namely: Planning, Implementation, Observation, and Reflection. The subjects of this study were grade IV students of SD GMIM 1 Madidir. Data collection techniques were in the form of observation and tests. The results of the first cycle of the study showed 67.32% and the second cycle showed 85.17%. The success of this study cannot be separated from the efforts of teachers in using learning models that are appropriate to the needs of students, namely Problem Based Learning (PBL). Thus, it can be said that the Problem Based Learning (PBL) learning model can improve the learning outcomes of Indonesian language in grade IV students of SD GMIM 1 Madidir.